Sosialisasi Hak dan Kewajiban Suami Istri Prespektif Hukum Islam pada Ibu-Ibu PWBI Kwala Bekala - Muhammad Hizbullah; Haidir Haidir; Syahrul Bakti Harahap; M. Guffar Harahap; Adawiyah Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
The balance between the rights and obligations of husband and wife is a fundamental pillar in building a harmonious household according to Islamic teachings. However, there is still a significant lack of understanding among the community, especially among women, regarding the roles and responsibilities of each partner in married life. This study aims to analyze the effectiveness of outreach activities regarding the rights and obligations of husband and wife from the perspective of Islamic Law, delivered to members of the PWBI (Persatuan Wanita Batak Indonesia) Kwala Bekala. The method used is a qualitative-descriptive approach, with data collection techniques including observation, interviews, and documentation during the outreach activity. The results of the study show that the outreach was effective in enhancing participants’ understanding of the fundamental principles of marital relationships in Islamic law, such as the concept of male leadership, consultation (shura), justice, and the importance of communication and mutual respect. The activity also had a positive impact on participants’ legal and religious awareness in managing their household lives. Such activities need to be expanded further to strengthen Muslim family resilience based on Islamic values.